2017
DOI: 10.1097/yco.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine use and dependence in vulnerable female populations

Abstract: Vulnerable populations of women at risk of methamphetamine abuse and dependence. Impacts on their physical and mental health, IPV, and pregnancy have been reported continuing, which guide that empowering and holistic substance abuse are necessary for specific group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
1
14
0
2
Order By: Relevance
“…The registered drug use identified as methamphetamine (MA) user increased from 29 to 43.8% in 2014 (Zhu et al, 2016 ). With East Asia regarded as a major region of concern due to its high MA production and trafficking (Rawson, 2013 ; Gowing et al, 2015 ; Kittirattanapaiboon et al, 2017 ), many researchers have raised an alert about ATS use/abuse around the world. The challenges of ATS use disorder have been recognized in China, and a large body of research on ATS use has emerged (Du et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The registered drug use identified as methamphetamine (MA) user increased from 29 to 43.8% in 2014 (Zhu et al, 2016 ). With East Asia regarded as a major region of concern due to its high MA production and trafficking (Rawson, 2013 ; Gowing et al, 2015 ; Kittirattanapaiboon et al, 2017 ), many researchers have raised an alert about ATS use/abuse around the world. The challenges of ATS use disorder have been recognized in China, and a large body of research on ATS use has emerged (Du et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies found that sleep duration is longer and sleep quality is higher on average in women than men (Knutson, 2013 ), women are diagnosed with depression and anxiety disorders roughly twice as often as men (Fattore et al, 2014 ). Current studies focus on specific vulnerable populations, such as sex workers and women with HIV (Rawson, 2013 ; Rodriguez et al, 2014 ; Zhang et al, 2015 ; Page et al, 2016 ; Kittirattanapaiboon et al, 2017 ). However, reports on the treatment of female ATS-dependent individuals are rare.…”
Section: Introductionmentioning
confidence: 99%
“…These results provide support that both environmental factors are correlated between them, independent of the ulterior development or exacerbation of SSD. In this line, previous reviews have already concluded that there is a positive association between childhood or adulthood trauma and substance use (Kittirattanapaiboon, Srikosai, & Wittayanookulluk, 2017;Konkolÿ Thege et al, 2017;Lijffijt, Hu, & Swann, 2014;Simpson & Miller, 2002), but the timing of the association is still unclear as most of the traumatic experiences are retrospectively self-reported. Therefore, longitudinal well-designed studies about this area are highly recommended to establish robust conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…10 Jahren wirdzunächst in den USA, dann in den europäischen Staatenein sehr starker Anstieg des Missbrauchs verzeichnet. Besonders im Bundesland Sachsen [19,20]. Methamphetamine weisen auch einen negativen Effekt auf die adulte myokardiale Funktion auf [21].…”
Section: Verbreitung Der Drogeunclassified